Stress, anxiety, and depression trajectories during the “first wave” of the COVID-19 pandemic: what drives resilient, adaptive and maladaptive responses in the Portuguese population? - Fernandes, Afonso; Ferreira, Sónia; Moreira, Pedro; Machado-Sousa, Mafalda; Couto, Beatriz; Raposo-Lima, Catarina; Costa, Patrício; Morgado, Pedro; Picó-Pérez, Maria (Frontiers in Public Health, 2024)
Introduction: The COVID-19 outbreak and the community mitigation strategies implemented to reduce new SARS-CoV-2 infections can be regarded as powerful stressors with negative consequences on people's mental health. Although it has been shown that negative emotional symptoms subside during lockdown, it is likely the existence of inter-individual differences in stress, anxiety and depression trajectories throughout lockdown.Objectives: We aimed to cluster participants' according to their trajectories of stress, anxiety and depression scores throughout lockdown, and identify the sociodemographic, clinical, and lifestyle factors that may distinguish the subjects included in the different clusters.Methods: From March 23, 2020, to May 31, 2020, participants completed weekly online questionnaires on sociodemographic information (age, sex, education level, and employment status), psychological functioning (DASS-21, NEO-FFI-20), and clinical data (psychiatric disorders, psychiatric medication, physical disorders). Data regarding smoking status, alcohol consumption, physical activity, and time spent daily looking for COVID-19-related information were also collected. Stress, anxiety and depression trajectories were determined using latent class mixed models.Results: A total of 2040 participants answered the survey at baseline and 603 participants answered all surveys. Three groups ("Resilient", "Recovered", and "Maladaptive") with distinct mental health trajectories were identified. Younger participants, women, participants with lower education level, not working, studying, diagnosed with a mental disorder, taking psychiatric medication, smokers, those who spent more time consuming COVID-19-related information and those with higher neuroticism tended to cluster in the "Maladaptive" group, placing them at higher risk of persistent negative emotional symptoms during compulsory confinement.Conclusion: Accordingly, a tailored approach to emotional suffering for vulnerable subjects during the COVID-19 and future pandemics must be devised.